Effect of Carcinogenic Substance (7,12 Dimethylbenz [a] Anthracene (DMBA)) on Tissue, Hematology Character and Enzyme Activity in Rat - Abdulridha Mohammed Al-Asady1, Ntisar Kadhum Ghaleb2, Abeer Muhammedali Jasim Alnasrawi3, Thoalffaka (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aimed to investigate the effects of 7,12 dimethylbenz [a] anthracene (DMBA) on some blood parameters and hepatic histopathology in rats and antioxidant enzyme. twenty female Wistar albino rats, weighing 180–200 g, were randomly divided into two group. DMBA group (positive group) who received 20 mg DMBA/kg body weight/ (single Douse). Control group (negative group) don’t received any thing. The animals in the groups were sacrificed at the end of the 90 days: The histological structure of the liver tissues in the control group was normal. the liver exhibited hydropic degeneration and coagulation necrosis in hepatocytes, severe dilation in the sinusoids, congestion in the central and portal regions , DMBA groups, was degenerative and necrotic changes were detected. MDA levels increased in the DMBA group , compared to the control group, Antioxidant activity CAT, SOD and GPX, the results showed increased enzyme activity in positive control compared with negative groups, ,the hematological parameter was increase in WBC, PLT, GRA, and LYM and decrease in RBC value .